Microbiologically influenced corrosion of mild steel in cultures of sulphate reducing bacteria - Dubey R.S.; Namboodhiri T.K.G.; Upadhyay S.N. (My University, 2025)
Microbiologically influenced corrosion (MIC) of mild steel samples were studied in two different bacterial strains, Pseudomonas fluorescens and Desulphovibrio vulgaris, isolated from cutting oil emulsions by potentiostatic polarization technique. The relationship between the corrosion behaviour and presence of biofilm on mild steel samples were determined. Bacteria were mixed with corrosion products hindering the formation of a protective layer. In both media, anodic depolarization was observed in the presence of ferric iron reducing bacteria. Anodic depolarization was achieved by the bacteria reduction of ferric to ferrous compounds. In the absence of the bacteria, both anode and cathode were polarized.